Commodification of Workers and Quality of Reporting on YouTube - Noerma Kurnia Fajarwati; Rizqi Fitrianti (Institute Of computer Science (IOCS), 2024)
In the digital era, a number of media use YouTube to distribute their content in order to gain new profit opportunities from social media. This research aims to determine the commodification of workers on YouTube and determine its impact on the quality of news. The research uses qualitative methods with a case study approach and data collection using documentation and literature studies. The results of this research found that the heavy work carried out by media workers and the minimal wages of media workers because they are not equivalent to a journalist's living wage mean that the practice of commodification is still ongoing. YouTube is one of the media's efforts to maintain its existence, so that the creativity of content creators becomes evidence of the commodification of workers which provides profits for the media. Regarding the quality of news, this research found that content creators generally only pursue what is common to public consumption, so the news that is broadcast is generally only done to meet normative quality standards